2013
DOI: 10.2478/auom-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Controlled G-Frames and Their G-Multipliers in Hilbert spaces

Abstract: Multipliers have been recently introduced by P. Balazs as operators for Bessel sequences and frames in Hilbert spaces. These are operators that combine (frame-like) analysis, a multiplication with a fixed sequence ( called the symbol) and synthesis. One of the last extensions of frames is weighted and controlled frames that introduced by P.Balazs, J-P. Antoine and A. Grybos to improve the numerical efficiency of iterative algorithms for inverting the frame operator. Also g-frames are the most popular generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…P. Balaz et al [3] introduced controlled frame to improve the numerical efficiency of interactive algorithms for inverting the frame operator. In recent times, several generalizations of controlled frame namely, controlled K-frame [22], controlled g-frame [23], controlled fusion frame [19], controlled g-fusion frame [28], controlled K-g-fusion frame [24] etc. have been appeared.…”
Section: Controlled K-g-fusion Framementioning
confidence: 99%
“…P. Balaz et al [3] introduced controlled frame to improve the numerical efficiency of interactive algorithms for inverting the frame operator. In recent times, several generalizations of controlled frame namely, controlled K-frame [22], controlled g-frame [23], controlled fusion frame [19], controlled g-fusion frame [28], controlled K-g-fusion frame [24] etc. have been appeared.…”
Section: Controlled K-g-fusion Framementioning
confidence: 99%
“…Controlled frames extended to g-frames in [17] and for fusion frames in [15]. In this section, the concept of controlled frames and controlled Bessel sequences will be extended to K-frames and it will be shown that controlled K-frames are equivalent K-frames.…”
Section: Controlled K-framesmentioning
confidence: 99%
“…The main advantage of these frames lies in the fact that they retain all the advantages of standard frames but additionally they give a generalized way to check the frame condition while offering a numerical advantage in the sense of preconditioning. Recent developments in this direction can be found in [14][15][16][17][18] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Basic properties and some applications of this operator for Bessel sequences, frames and Riesz basis have been proved by Peter Balazs in his Ph.D habilation [3]. Recently, the concept of multipliers extended and introduced for continuous frames [6], fusion frames [2], p-Bessel sequences [26], generalized frames [25], controlled frames [27], Banach frames [12,13], Hilbert C * -modules [23] and etc. The symbol of m has important role in the studying of multiplier operators.…”
Section: Preliminariesmentioning
confidence: 99%